Straightforward Access to Terpene-Based 1,2-Diols and Their Acetals as Fragrance Ingredients - Stefanow, Vivian; Kell, Lukas; Leduskrasta, Aiga; Eh, Marcus; Panten, Johannes; Werner, Thomas (The Journal of Organic Chemistry)
Keywords: T4; CSSD

Design, isolation, synthesis, and mechanistic insight of flavonoids isolated from Beilschmiedia obscura, as potential α-glucosidase inhibitors - Nyemeck, Suzanne L.; Eyong, Kenneth O.; Bidingha, Ronald; Kamdem, Michael HK.; Ndinteh, Derek T.; Odumosu, Patricia O.; Folefoc, Gabriel N.; Bilanda, Danielle C.; Egbe, Andrew E.; Werner, Thomas; Bekono, Boris D.; Ntie-Kang, Fidele (Phytochemistry Letters)
Keywords: T4

Lupane derivatives: Design, isolation, synthesis and evaluation of antiplasmodial activity against Plasmodium falciparum 3D7 strain - Yemback, Pierre; Eyong, Kenneth O.; Efange, Noella M.; Kamdem, Michael HK.; Ndinteh, Derek T.; Odumosu, Patricia O.; Folefoc, Gabriel N.; Ayong, Lawrence; Werner, Thomas (Phytochemistry Letters)
Keywords: T4

Chemoenzymatic Synthesis of Chiral Building Blocks Based on the Kinetic Resolution of Glycerol‐Derived Cyclic Carbonates - Terazzi, Constanza; Spannenberg, Anke; von Langermann, Jan; Werner, Thomas (ChemCatChem)
Abstract The biocatalytic kinetic resolution of cyclic carbonates derived from glycerol is reported. A selection of 26 esterases and lipases was tested for the asymmetric hydrolysis of the model substrate (epichlorohydrin carbonate) in aqueous medium. Among them, Pig Liver Esterase and Novozym® 435 showed the best selectivity with E =38 and 49, respectively. Both enzymes were employed for the conversion of 12 glycerol derivatives under optimized conditions. The resolution of halogenated carbonates afforded the unconverted enantiomer in up to >99 : 1 er . Furthermore, Novozym® 435 was successfully recycled 10 times without significant loss of activity. Upscaling and isolation of the chiral carbonate was also demonstrated. Subsequent conversion of this chiral building block allowed the direct one‐pot synthesis of ( S )‐Guaifenesin, ( S )‐Mephenesin and ( S )‐Chlorphenesin in up to 89 % yield and 94 : 6 er .
Keywords: T1; T4; CSSD

Base-Free Catalytic Wittig-/Cross-Coupling Reaction Sequence as Short Synthetic Strategy for the Preparation of Highly Functionalized Arylbenzoxepinones - Werner, Thomas; Grandane, Aiga; Pudnika, Linda; Domraceva, Ilona; Zalubovskis, Raivis (Synthesis)
Abstract The facile synthesis of highly functionalized building blocks with potential biological activity is of great interest to medicinal chemistry. The benzoxepinone core structures commonly exhibit biological activity. Thus, a short and efficient synthetic route towards benzoxepine containing scaffold, which enables late stage modification was developed. Namely, base-free catalytic Wittig reactions enabled the synthesis of bromobenzoxepinones from readily available starting materials. Subsequent, Suzuki–Miyaura and Stille reactions proved to be suitable methods to access a variety of benzoxepinone diaryl derivatives by late stage modification in only three steps. This three-step reaction sequence is suitable for high throughput applications and gives facile access to highly complex molecular structures, which are suitable for further functionalization. The antiproliferative properties of selected arylbenzoxepinones were tested in vitro on monolayer tumor cell line A549. Notably, in this initial screening, these compounds were found to be active in the micromolar range.
Keywords: T2; T4; CSSD

Stereoselective Synthesis of acis-Cedrane-8,9-diol as a Key Intermediate for an Amber Odorant - Stefanow, Vivian; Grandane, Aiga; Eh, Marcus; Panten, Johannes; Spannenberg, Anke; Werner, Thomas (Organic Process Research & Development)
Keywords: T4; CSSD

Stereoselective Synthesis of acis-Cedrane-8,9-diol as a Key Intermediate for an Amber Odorant - Stefanow, Vivian; Grandane, Aiga; Eh, Marcus; Panten, Johannes; Spannenberg, Anke; Werner, Thomas (Organic Process Research & Development)
Keywords: T4; CSSD

AMPA-15N – Synthesis and application as standard compound in traceable degradation studies of glyphosate - Wirth, Marisa A.; Longwitz, Lars; Kanwischer, Marion; Gros, Peter; Leinweber, Peter; Werner, Thomas (Ecotoxicology and Environmental Safety)
Keywords: T4; CSSD

Reduction of Activated Alkenes by PIII/PV Redox Cycling Catalysis - Longwitz, Lars; Werner, Thomas (Angewandte Chemie)
Abstract The carbon–carbon double bond of unsaturated carbonyl compounds was readily reduced by using a phosphetane oxide catalyst in the presence of a simple organosilane as the terminal reductant and water as the hydrogen source. Quantitative hydrogenation was observed when 1.0 mol % of a methyl‐substituted phosphetane oxide was employed as the catalyst. The procedure is highly selective towards activated double bonds, tolerating a variety of functional groups that are usually prone to reduction. In total, 25 alkenes and two alkynes were hydrogenated to the corresponding alkanes in excellent yields of up to 99 %. Notably, less active poly(methylhydrosiloxane) could also be utilized as the terminal reductant. Mechanistic investigations revealed the phosphane as the catalyst resting state and a protonation/deprotonation sequence as the crucial step in the catalytic cycle.
Keywords: T2; T4

Novel processes for preparing cis-cedrandiol - Werner, Thomas; Stefanow, V.; Grandane, A.; Panten, J.; Eh, M.
Keywords: T4

Reduction of Activated Alkenes by PIII/PV Redox Cycling Catalysis - Longwitz, Lars; Werner, Thomas (Angewandte Chemie International Edition)
Abstract The carbon–carbon double bond of unsaturated carbonyl compounds was readily reduced by using a phosphetane oxide catalyst in the presence of a simple organosilane as the terminal reductant and water as the hydrogen source. Quantitative hydrogenation was observed when 1.0 mol % of a methyl‐substituted phosphetane oxide was employed as the catalyst. The procedure is highly selective towards activated double bonds, tolerating a variety of functional groups that are usually prone to reduction. In total, 25 alkenes and two alkynes were hydrogenated to the corresponding alkanes in excellent yields of up to 99 %. Notably, less active poly(methylhydrosiloxane) could also be utilized as the terminal reductant. Mechanistic investigations revealed the phosphane as the catalyst resting state and a protonation/deprotonation sequence as the crucial step in the catalytic cycle.
Keywords: T2; T4; CSSD

Benzoxepinones: A new isoform-selective class of tumor associated carbonic anhydrase inhibitors - Grandane, Aiga; Nocentini, Alessio; Werner, Thomas; Zalubovskis, Raivis; Supuran, Claudiu T. (Bioorganic and Medicinal Chemistry)
Keywords: T4; T2; CSSD

Life Cycle Assessment for the Organocatalytic Synthesis of Glycerol Carbonate Methacrylate - Büttner, Hendrik; Kohrt, Christina; Wulf, Christoph; Schäffner, Benjamin; Groenke, Karsten; Hu, Yuya; Kruse, Daniela; Werner, Thomas (ChemSusChem)
Keywords: T1; T4; CSSD

Catalytic Approaches to Monomers for Polymers Based on Renewables - Stadler, Bernhard M.; Wulf, Christoph; Werner, Thomas; Tin, Sergey; de Vries, Johannes G. (ACS Catalysis)
Keywords: T4; CSSD

Intramolecular Base-Free Catalytic Wittig Reaction: Synthesis of Benzoxepinones - Grandane, Aiga; Longwitz, Lars; Roolf, Catrin; Spannenberg, Anke; Murua Escobar, Hugo; Junghanss, Christian; Suna, Edgars; Werner, Thomas (The Journal of Organic Chemistry)
Keywords: T2; T4; CSSD

Calcium-Based Catalytic System for the Synthesis of Bio-Derived Cyclic Carbonates under Mild Conditions - Longwitz, Lars; Steinbauer, Johannes; Spannenberg, Anke; Werner, Thomas (ACS Catalysis)
Keywords: T1; T3; T4; CSSD

Calcium-Based Catalytic System for the Synthesis of Bio-Derived Cyclic Carbonates under Mild Conditions - Longwitz, Lars; Steinbauer, Johannes; Spannenberg, Anke; Werner, Thomas (ACS Catalysis)
Keywords: T1; T3; T4